Linguagem, espaço e nação: um mapeamento das identidades multigeográficas do protagonista imigrante - Cecily Raynor (Estudos de Literatura Brasileira Contemporânea)
In this paper, I analyze works portraying migration:Estive em Lisboa e lembrei devocê(2009), by Luiz Ruffatto, a work centered on the story of a Brazilian migrantto Lisbon, andMar Paraguayo(1992 ), by Wilson Bueno, which recounts the taleof a Paraguayan prostitute living inGuaratuba. Specifically, I argue thatcontemporary migration-themed novels challenge, stretch and/or interruptnarrative time-space cohesion by obscuring, often gradually, the boundaries between the national and transnational. I examine space both in theconcretesense, in domestic and urban realms, as well as metaphorically. Within thisexpanded theoretical framework, I argue that these works not only test the ideaof space, but also generate new or alternative spatial possibilities from which wecan observe the construction and maintenance of identity.